Koordinasi Pengembangan Pariwisata Pantai Paris Sebagai Potensi Wisata Di Tigaras Kecamatan Dolok Pardamean Kabupaten Simalungun - Corry Debora Nainggolan; Tunggul Sihombing (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
Coordination is carried out to create a uniform and harmonious effort on the target that has been determined. The ideal coordination in tourism development is coordination that is able to establish effective cooperation and communication between related organizations so that each organization is able to carry out its duties in order to achieve effectiveness in the implementation of tourism development, one organizational unit will not be able to run alone without cooperating with other organizations. The research method used in this study is a descriptive research method with a qualitative approach. By formulating the theory put forward by Dann Sugandha, namely units or organizations, potential sources, movement of activities, unity, harmony, the same direction (target). By using data collection techniques carried out by means of interviews, observations, and documentation The results of this study are that in developing the Paris Beach destination in Tigaras, the Department of Tourism and Culture coordinates directly with the Department of Transportation to regulate land and water traffic, which then coordinates also with the Department of Public Works regarding Spatial Planning, facilities and infrastructure, and coordination as well. carried out to the Tourism Awareness Group and the tourism management community in managing tourist destinations. The coordination of the development of these tourist destinations has the same direction and target, namely to make Paris Beach a tourist destination that will be taken into account and attract a lot of tourists, of course, with improvements such as road access to Paris Beach, the available rides are still suitable for use, and comfort of visitors on Paris Beach. From the results above, the coordination of the development of the Paris Beach has been carried out well but needs to be maximized.